Productivity of Islamic Banking in Indonesia - Fajra Octrina; Alia Gantina Siti Mariam (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
One measurement tool to increase banking performance, especially Islamic banking, is from the productivity side. Productivity measurement is done to determine how far a bank can run its operational activities by minimalizing input and maximalizing output results. This study aims to analyze the productivity level of Islamic Banking in Indonesia. The research sample was 11 Islamic banks from 2010 to 2019. Data obtained through financial statements and then divided into input and output variables. The productivity measurement technique by using Malmquist Index. The research shows that Islamic banking productivity with a cost approach indicates that Islamic banking has achieved a productive stage. It is seen from the average TFPCH (Total Factor Productivity Change) score that is quite high. It indicates that the decrease in Indonesia's Islamic banking growth generally occurs due to technology change